2015
DOI: 10.1590/1678-7153.201528120
|View full text |Cite
|
Sign up to set email alerts
|

O reduzido envolvimento social: implicações para o ajustamento psicossocial de crianças em contexto pré-escolar

Abstract: ResumoO reduzido envolvimento social, aspeto central na defi nição da solidão social, foi analisado numa amostra de 337 crianças portuguesas (171 rapazes), com idades compreendidas entre os três e os cinco anos. Com base em metodologias de observação, realizadas em contexto de Jardim de infância, verifi cou-se que níveis reduzidos de envolvimento social estão negativamente associados a baixos níveis de competência social, de resiliência e de um elevado ego-controle. A aceitação pelos pares, o impacto e a prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
2
4
0
4
Order By: Relevance
“…On the other hand, Portuguese psychologists also anticipated that withdrawing from social situations and peer interactions can prevent inhibited preschoolers from engaging in developmentally important learning experiences and from developing age-appropriate social and socio-cognitive skills, such as learning about social environments and how to behave within them, interpersonal negotiation and perspective-taking, understanding others' thoughts and emotions and the self in relation to others . These findings are consistent with prior studies conducted in Portuguese samples, showing that preschool children who exhibit lower levels of social engagement display lower levels of social competence than their peers, when using broadband assessments that include affect expression within social transactions and the ability to modulate it successfully to achieve goals within the social group (Santos, Daniel, Antunes, Coppola, Trudel, & Vaughn, 2020;Santos, Monteiro, Sousa, Fernandes, Torres, & Vaughn, 2015;Vaughn et al, 2016). The emphasis of Portuguese psychologists on the idea that emotional abilities are non-dissociable from social competence (Santos et al, 2020) may reflect the salience of sociability and emotional expressiveness in Southern European cultures (Casiglia et al, 1998).…”
Section: Perceptions Of Portuguese Psychologists About the Consequences Of Bi/sw For Child's Socioemotional Adjustmentsupporting
confidence: 90%
“…On the other hand, Portuguese psychologists also anticipated that withdrawing from social situations and peer interactions can prevent inhibited preschoolers from engaging in developmentally important learning experiences and from developing age-appropriate social and socio-cognitive skills, such as learning about social environments and how to behave within them, interpersonal negotiation and perspective-taking, understanding others' thoughts and emotions and the self in relation to others . These findings are consistent with prior studies conducted in Portuguese samples, showing that preschool children who exhibit lower levels of social engagement display lower levels of social competence than their peers, when using broadband assessments that include affect expression within social transactions and the ability to modulate it successfully to achieve goals within the social group (Santos, Daniel, Antunes, Coppola, Trudel, & Vaughn, 2020;Santos, Monteiro, Sousa, Fernandes, Torres, & Vaughn, 2015;Vaughn et al, 2016). The emphasis of Portuguese psychologists on the idea that emotional abilities are non-dissociable from social competence (Santos et al, 2020) may reflect the salience of sociability and emotional expressiveness in Southern European cultures (Casiglia et al, 1998).…”
Section: Perceptions Of Portuguese Psychologists About the Consequences Of Bi/sw For Child's Socioemotional Adjustmentsupporting
confidence: 90%
“…Estas crianças apresentam dificuldades em regular a ansiedade e o medo sentido, o que resulta frequentemente no evitamento ou retirada destas interações, mantendo-se à margem do grupo (Rubin & Barstead, 2018). Tendem, ainda, a minimizar e inibir as suas emoções, utilizando estratégias menos assertivas ao iniciar interações, sendo frequentemente ignoradas pelos pares (e.g., Santos et al, 2015). As suas dificuldades tornam-nas mais dependentes dos adultos (e.g., Coplan & Prakash, 2003), bem como parceiros de brincadeira pouco atrativos aos olhos dos pares, encontrando-se em maior risco de rejeição e vitimização, em particular após os anos pré-escolares (e.g., Rubin & Barstead, 2018;Rubin et al, 2009).…”
Section: Palavras-chaveunclassified
“…Estas crianças tendem a manifestar de modo consistente e a longo prazo baixas competências sociais e relacionais, auto-estima negativa, sentimentos de solidão e inclusive depressão (e.g., Gazelle & Rudolph, 2004;Markovic & Bowker, 2017;Rubin et al, 2009). Contrariamente à agressividade são poucos os resultados que referem diferenças em função do sexo em termos da prevalência destes comportamentos (e.g., Diener & Kim, 2004), no entanto, as consequências parecem ser mais negativas para os rapazes, do que para as raparigas (Rubin et al, 2009;Santos et al, 2015).…”
Section: Palavras-chaveunclassified
“…In Portugal, the LatinX tradition increasingly coexist with individualistic values (Wall & Gouveia, 2014). Recent Portuguese empirical studies (Santos et al, 2015) and US-Portugal comparisons (Vaughn et al, 2016) have shown that preschoolers who displayed low social engagement were less visible for peers and less likely to be chosen as preferred playmates by peers. Associations between AW and sociometric measures of negative peer outcomes have been also observed among Portuguese adolescents (Correia, Santos, Freitas, Ribeiro, & Rubin, 2014).…”
Section: The Influence Of Culture On Peer Attitudes and Responses Towmentioning
confidence: 99%